"Almost Equal": Confronting Norms and Normality in Experiencing Visual Disability. (November 2021) - Porkertová, Hana
This article examines the everyday experience of visually disabled people with norms and normality and confronts it with three approaches discussed in disability studies: (i) the medical model, (ii) the social model, and (iii) critical disability studies. The most available model to the people in the study, as well as the most widespread approach in Czech society, is the medical model. However, the text shows that although other approaches are rather marginal, their logic is present in the everyday experience of the communication partners in the research. They can espouse the rigid, medical model, while, at the same time, confronting the construction of norms that both the social model and critical disability studies defy. This finding reveals both the normative and subversive character of disability, manifested in visually impaired experience.